Proyecto de factibilidad para creación de una empresa de asesoramiento y capacitación en seguridad y salud ocupacional en la ciudad de Santo Domingo - Vivanco Aguirre, Nora Patricia (2015)
The research was conducted in the city of Santo Domingo, aiming at presenting a proposal for the "PROJECT FEASIBILITY FOR CREATING BUSINESS ADVISORY AND TRAINING IN OCCUPATIONAL SAFETY AND HEALTH. Then in materials and methods of data collection techniques and research methods that were served to the development of our study are presented. Among the methods used are inductive, deductive, descriptive, analytical and statistical method. Techniques were applied to gather information, such as the questionnaire and survey of a select group of companies to determine if they would be willing to use the service of advice and training in Occupational Safety and Health, identify the characteristics of the service, appropriate price to place the service. The market survey conducted in the city of Santo Domingo, with a sample of 299 companies and 2 training enterprises; Weighted surveys have been analyzed and the results have been inferred then perform market analysis, determining the potential demand of 239 companies, Real Demand 149 companies, 5,960 Effective Demand training and advisory services, the offer of 600 services training and counseling, and 5,360 unmet demand training and advisory services, which allowed us to determine that the project can and should be run by the results obtained in the analysis of demand, supply and marketing levels of this service. The installed capacity of the project determines that the company will be able to offer 4,360 training and advisory services, and whose capacity utilization is 3,024 training and advisory services, of which 70% capacity utilization for the first year will be offered corresponding to 3024 training services, counseling, locating it to be located in the city of Santo Domingo in the streets Av is determined. Abraham Calazacón and Calle Paz. The service process demands the use of suitable equipment, which will guarantee for quality service at reasonable prices. Then the project engineering process diagrams determining the characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures develops. Also an administrative study determined as a Limited Liability Company, and the functional organizational structure hierarchical levels both Legislative, Executive, Consultant Level Support Assistant, Operational Level Level as well as operating manuals, charts was performed; which served as a guideline for implementing a good organization, since there will be the following personnel: Manager, Secretariat, Contadora, trainers, who will be part of the Administrative staff and operational staff distributed as follows: one and commercial advisor . The project reaches an investment of $ 28,805.69 and will be financed with contributions from partners the 65.28% of the total investment corresponding to $ 18,805.69 and a loan that will keep the project with the National Finance Corporation will be the 34.72% which corresponds to $ 10,000 a 10 year term at 15% annual interest. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 82346,91, which indicates that the project or investment is suitable. For this project IRR is 73,15%, this being satisfactory value for the project, the time it would take to recover the original investment would be 1 year, 4 months and 11 days, for this project, the sensitivity values are less than one, so do not affect the project changes in costs and increased revenues decreased 22,60% and 16,20%, respectively, ie the project is not sensitive to these changes. Then the conclusions and recommendations of the project significant raises